Rancang Bangun Chatbot Untuk Meningkatkan Performa Bisnis - Amalia, Eka Larasati; Wibowo, Dimas Wahyu (Jurnal Ilmiah Teknologi Informasi Asia, 2019)
Chatbot is an application / service that interacts with custumers through text conversations. Chatbot works to replace the role of humans in serving talks through the messaging application. Chatbot has become more popular in today's business groups because Bot ensures that all messages from customers can be handled quickly and companies can save on operational costs. In addition, with the chatbot, business premises can provide active services for 24 hours. In this study Chatbot will be designed to use Chatfuel to develop a business. In this built bot can help business owners to record orders, process orders, record customers, business location information and facilitate payment transactions